2015
DOI: 10.1016/j.jinteco.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Neoclassical growth and the natural resource curse puzzle

Abstract: The traditional view that natural riches increase the wealth of nations has been recently challenged by empirical …ndings that point out that natural inputs are negatively related to growth. This paper shows, within a two-sector neoclassical growth model with international trade in goods, that these two views can be reconciled. Natural inputs directly a¤ect both long-run income and transitional growth. These two e¤ects can be positive or negative depending on input elasticities. Furthermore, they go in opposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Similar results for the US states can be found inBoyce and Emery (2011) andGuilló and Perez-Sebastian (2015), from a theoretical and empirical point of view.4 James (2015a) also provides evidence of this fact using cross-country data during certain periods which are selected in order to follow oil price booms and busts. In contrast, for a set of countries,Alexeev and Conrad (2009) show that mineral resources in general have a positive impact on per capita income levels.…”
mentioning
confidence: 58%
“…Similar results for the US states can be found inBoyce and Emery (2011) andGuilló and Perez-Sebastian (2015), from a theoretical and empirical point of view.4 James (2015a) also provides evidence of this fact using cross-country data during certain periods which are selected in order to follow oil price booms and busts. In contrast, for a set of countries,Alexeev and Conrad (2009) show that mineral resources in general have a positive impact on per capita income levels.…”
mentioning
confidence: 58%
“…In developing a wider understanding of the domestic implications of energy resource exports, the so called "resource curse" or "paradox of plenty" [31][32][33][34] is relevant and should be considered. At a high level, the basic premise of the resource curse is that without careful governance and financial management, countries experiencing a significant increase in GDP due to natural resource exports have frequently experienced considerable wider negative economic outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The argument that resource abundance and dependence may lead to slower economic growth is not new. The resource curse hypothesis is a phenomenon frequently associated with the "Dutch disease" effect caused by some exogenous influence, such as trade liberalization or a resource price boom (Gelb, 1988;Gylfason, 2001). According to Sachs and Warner (1995), dependence on natural resources negatively affects economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This became evident when resource‐rich countries such as Venezuela, Nigeria, and the Republic of Congo experienced lower growth; while countries with limited resources, such as Singapore, South Korea, and others experienced buoyant growth per capita (Lotfalipour & Salehnia, 2022). This discovery led to growing research into examining the effect of natural resources on economic growth (Dramani et al, 2022; Guilló & Perez‐Sebastian, 2015; Kim & Lin, 2017; Rjoub et al, 2021). Using quantitative analysis to examine the neoclassical growth and the natural resource curse puzzles within 49 states in the United States of America, Guilló and Perez‐Sebastian (2015) defined resource‐rich and poor groups of states in different ways and found that 10% richest states on average, 1.39% points slower than the 10% resource‐poor.…”
Section: Literature Reviewmentioning
confidence: 99%